Effects of UGT2B7, SCN1A and CYP3A4 on the therapeutic response of sodium valproate treatment in children with generalized seizures. (May 2018) - Feng, Weixing; Mei, Shenghui; Zhu, Leting; Yu, Yazhen; Yang, Weili; Gao, Baoqin; Wu, Xiaojuan; Zhao, Zhigang; Fang, Fang
Highlights: rs7668282 was more prevalent in drug-resistant patients than drug-responsive patients. rs2242480 and rs10188577 were more prevalent in drug-resistant patients than drug-responsive patients. Polymorphisms of UGT2B7, CYP3A4, and SCN1A genes were associated with VPA efficacy. Abstract: Purpose: This study aims to evaluate the associations between genetic polymorphisms and the effect of sodium valproate (VPA) therapy in children with generalized seizures. Methods: A total of 174 children with generalized seizures on VPA therapy were enrolled. Steady-state trough plasma concentrations of VPA were analyzed. Seventy-six single nucleotide polymorphisms involved in the absorption, metabolism, transport, and target receptor of VPA were identified, and their associations with the therapeutic effect (seizure reduction) were evaluated using logistic regression adjusted by various influence factors. Results: rs7668282 ( UGT2B7, T > C, OR = 2.67, 95% CI: 1.19 to 5.91, P = 0.017) was more prevalent in drug-resistant patients than drug-responsive patients. rs2242480 ( CYP3A4, C > T, OR = 0.27, 95% CI: 0.095 to 0.79, P = 0.017) and rs10188577 ( SCN1A, T > C, OR = 0.40, 95% CI: 0.17 to 0.94, P = 0.035) were more prevalent in drug-responsive patients compared to drug-resistant patients. Conclusion: In children with generalized seizures on VPA therapy, polymorphisms of UGT2B7, CYP3A4, and SCN1A genes were associated with seizure reduction. Larger studies are warranted to corroborate the results.